Towards overcoming obstacles of type II photodynamic therapy: Endogenous production of light, photosensitizer, and oxygen - Lin Yu; Zhen Liu; Wei Xu; Kai Jin; Jinliang Liu; Xiaohui Zhu; Yong Zhang; Yihan Wu (Elsevier, 2024)
Conventional photodynamic therapy (PDT) approaches face challenges including limited light penetration, low uptake of photosensitizers by tumors, and lack of oxygen in tumor microenvironments. One promising solution is to internally generate light, photosensitizers, and oxygen. This can be accomplished through endogenous production, such as using bioluminescence as an endogenous light source, synthesizing genetically encodable photosensitizers in situ, and modifying cells genetically to express catalase enzymes. Furthermore, these strategies have been reinforced by the recent rapid advancements in synthetic biology. In this review, we summarize and discuss the approaches to overcome PDT obstacles by means of endogenous production of excitation light, photosensitizers, and oxygen. We envision that as synthetic biology advances, genetically engineered cells could act as precise and targeted "living factories" to produce PDT components, leading to enhanced performance of PDT.